Análisis del impacto ambiental de residuos sólidos en la Universidad Técnica De Cotopaxi en el edificio matriz de esta institución con el diseño de un sistema de gestión para la disposición final. - Cumbicus Yungan, Diego Mauricio (2017)
This project aimed to carry out a study on the environmental impact of solid waste at Technical University of Cotopaxi, so to design a management system to identify, separate and classify them finding to contribute and to reduce the negative consequences that this problem brings as a consequence for Human and Environmental health. For this purpose, three research instruments were applied: a survey of employees linked to the study object, an observation guide and a Leopold matrix, responsible for establishing the different levels of impact generated. According to the calculations made, it is proposed to establish a new solid waste management system or independent process of each of the four blocks in which the parent building is structured as well as the location, quantity and volume of the calculated municipal dump (30 kilograms each one) from their identification (organic waste, paper and cardboard, glass and plastics). The main conclusions are that the proposed management system, this is extremely important, not only for the environmental impact of the institution, also for the sector where it is located, the efforts aimed at minimizing the waste generated by the different areas of the university have led to several strategies and preventive tools to minimize cleaning costs and reduce environmental pollution, but they have been insufficient and the proposed environmental solutions are efficient and fast to implement and contribute to reduce the problems that exist in the Technical University of Cotopaxi with the theme of environmental pollution.